Ultrahigh hardness with exceptional thermal stability of a nanocrystalline CoCrFeNiMn high-entropy alloy prepared by inert gas condensation. (October 2020) - Wang, Junjie; Wu, Shangshu; Fu, Shu; Liu, Sinan; Yan, Mengyang; Lai, Qingquan; Lan, Si; Hahn, Horst; Feng, Tao
Abstract: (CoCrFeNi)93.5 Mn6.5 nanocrystalline high-entropy alloy (nc-HEA) with an average grain size of 25 nm was prepared by inert gas condensation (IGC) using a laser evaporation source. An unprecedented increment in hardness was found from 484 HV to 791 HV after annealing at 600 °C for 1 h. More surprisingly, the original high hardness is maintained even after annealing at 1100 °C, which demonstrates superb thermal stability of the nc-HEA. The underlying strengthening mechanism is attributed to the unique microstructure of the nc-HEA and its evolution during annealing. This study provides a new preparation technique (laser-IGC) for high-performance nc-HEAs with great potential for applications. Graphical abstract: Image, graphical abstract